IMPLEMENTASI HIDDEN CURRICULUM DALAM RANGKA PEMBENTUKAN KARAKTER RELIGIUS DI MADRASAH ALIYAH NEGERI 1 PONOROGO - Wahkid Saputra, Ikhsan; M. Zainal Arif; Anip Dwi Saputro (LPPM STAI Muhammadiyah Probolinggo, 2024)
Education functions to develop the potential and shape the character of individuals holistically. The existing formal curriculum places more emphasis on cognitive aspects, so it needs to be supplemented with a hidden curriculum that focuses on character development through non-academic experiences in the school environment. The active role of the principal, teachers, and parents is very important in optimizing the formation of students' character through the hidden curriculum, which includes values, norms, habituation, and the cultivation of good ethics. This study examines the implementation of the hidden curriculum in forming religious character at Madrasah Aliyah Negeri (MAN) 1 Ponorogo, focusing on the implementation, outcomes, as well as supporting and inhibiting factors. The approach used is descriptive qualitative with data collection techniques of observation, in-depth interviews, and documentation. The results show that the hidden curriculum at MAN 1 Ponorogo is implemented through habituation activities such as morning prayers before starting lessons, congregational Zuhur prayers, Quran recitation, teacher role models, the culture of shaking hands when arriving at the madrasah, as well as the management of a religious and conducive learning environment. This curriculum contributes to shaping values such as honesty, responsibility, discipline, and respect. Supporting factors include the commitment of the madrasah principal, the active role of teachers, and the deeply rooted religious culture. The main obstacles are the lack of awareness among students due to their diverse backgrounds and the absence of formal assessment in the report cards.